(untitled) (NAU Journal of Technology and Vocational Education, 2024)
This study was carried out to ascertain the office competencies required of business education graduates for effective performance in modern offices in Imo State. Two research questions guided the study and two null hypotheses were tested at 0.05 level of significance. Descriptive survey research design was adopted for the study. The population of the study consisted of 201 managers in private and public organizations in Imo State. There was no sampling. A structured questionnaire containing 17 items was used for data collection. The instrument was validated by experts in the field of business education in the Department of Technology and Vocational Education and measurement and evaluation unit of the Department of Educational Foundation. Pilot test was used to establish the reliability of the instrument and Cronbach alpha was used to obtain the reliability coefficients of 0.97 and 0.94 for clusters B1 to B2 respectively with an overall coefficient of 0.96. One hundred and eighty nine duly completed copies of the questionnaire were retrieved and used for data analysis. Mean and standard deviation were used to answer the research questions and to determine the homogeneity of the respondents’ ratings while the z-test was used to test the null hypotheses. Findings revealed that respondents agreed that electronic publishing and electronic collaborative competencies were required of business education graduates for effective performance in modern offices. The findings also showed that ownership of organizations was not a significant factor on managers’ ratings of competencies required of business education graduates for effective performance in modern offices. The researchers concluded that equipping business education students with these competencies will help them to performance office tasks effectively when employed in business organizations upon graduation. It was recommended among others that business education lecturers should lay more emphasis on equipping their students with electronic publishing and electronic collaborative competencies identified by respondents as required by business education graduates for effective performance in modern offices